The efficiency of public secondary school principals in the Giza District Education Directorate in managing time in light of the Corona pandemic from the teachers’ point of view - Al-Zaben, Abdul-Rahman Finkhair Atallah Al-Ruwaished (Journal of Educational and Psychological Sciences, 2022)
The aim of the research is to identify the degree of efficiency of secondary government school principals in the Directorate of Education for the Giza District in managing time in light of the Corona pandemic from the teachers’ point of view, and to achieve the objectives of the study, the study sample was selected by the available method, and the questionnaire was used for the purposes of data collection after the psychometric characteristics were extracted. It has (honesty and stability), which consisted of (241) teachers, and the use of the descriptive analytical approach as it is the most appropriate to achieve the objectives of this study, and the results of the study indicated that the degree of efficiency of secondary government school principals in the Directorate of Education of the Giza District in managing time in light of the Corona pandemic from The teachers’ point of view was medium, and there were no statistically significant differences for the study variables (gender, experience, and educational qualification) in the efficiency of secondary government school principals in the Giza District Education Directorate in managing time in light of the Corona pandemic from the teachers’ point of view, and the study recommended providing courses Training for managers and directors in order to train on modern means of communication in order to facilitate the completion of tasks quickly and easily.